A TDMA-based mechanism to enforce real-time behavior in WiFi networks - Ricardo Moraes (2008)
In this paper, a TDMA-based mechanism is proposed for IEEE 802.11 Wireless LANs. This mechanism prioritizes real-time traffic in IEEE 802.11 networks, allowing the coexistence of standard stations with modified (real-time) stations in the same network-domain. The worst-case timing analysis of the TDMA-based mechanism shows that the service interval is upper-bounded, even when the communication medium is shared with timing unconstrained stations.